2013
DOI: 10.1016/j.amepre.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The Seamos Saludables Study

Abstract: Background Latinas in the U.S. are less physically active than non-Latino white women, and also report higher levels of diabetes, obesity, and other conditions related to inactivity. Interventions are needed to address disparities in this high-risk group. Purpose To evaluate the efficacy of a culturally adapted, Spanish-language, individually tailored, computer expert system–driven physical activity print-based intervention for adult Latinas. Design RCT. Setting/participants Participants were 266 inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 53 publications
1
69
2
Order By: Relevance
“…19,20 Adult women (aged 18 to 65 years) who self-identified as Hispanic or Latina, could read and write in Spanish, and were underactive (<60 minutes of MVPA/week) were recruited for participation in the trial. A total of 132 participants (mean age = 41.6 + 10.1 years; mean body mass index = 25.6+4.3 kg/m 2 ) were randomized to a 12 month print-based physical activity intervention.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Adult women (aged 18 to 65 years) who self-identified as Hispanic or Latina, could read and write in Spanish, and were underactive (<60 minutes of MVPA/week) were recruited for participation in the trial. A total of 132 participants (mean age = 41.6 + 10.1 years; mean body mass index = 25.6+4.3 kg/m 2 ) were randomized to a 12 month print-based physical activity intervention.…”
Section: Methodsmentioning
confidence: 99%
“…19,20 In an effort to more clearly understand the impact of individual components of the intervention, all participants were asked to wear a physical activity monitor (Omron HJ 720-ITC, Omron Health Care, Inc.) every day for 12 months that measured total steps and moderate intensity aerobic steps (100+ steps/minute) at both hourly and daily intervals. This detailed, longitudinal surveillance data will allow us to examine individual variability of physical activity over the course of an entire year.…”
mentioning
confidence: 99%
“…Six-month main trial MVPA outcomes and a description of the protocol are reported elsewhere. 15,16 Intervention participants ( n =132) received materials through the mail 11 times during the first 6 months, then booster doses at 8, 10, and 12 months, with a final assessment at 12 months. Spanish-language materials were individually tailored based on participants’ responses to monthly questionnaires about their thoughts, feelings, and behaviors surrounding MVPA, and were culturally adapted for Latinas based on extensive formative research (e.g., translation/back-translation, focus groups on barriers/intervention preferences for Latinas, cognitive interviews to ensure translation of key intervention messages, adaption of materials for low literacy levels 17 .…”
Section: Methodsmentioning
confidence: 99%
“…Nearly half (46%) had some college education, 25% did not finish high school, and 53.6% had a yearly family income <$20,000. A full description of the study sample is published elsewhere (Pekmezi et al, 16 Marcus and colleagues 15 ). Of the 266 randomized participants, 215 (81%) provided data at 12 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation